2020
DOI: 10.3390/ijerph17082869
|View full text |Cite
|
Sign up to set email alerts
|

Central American Immigrant Parents’ Awareness, Acceptability, and Willingness to Vaccinate Their Adolescent Children Against Human Papillomavirus: A Pilot Cross-Sectional Study

Abstract: Despite increasing interest in understanding the factors influencing awareness and acceptability of the human papillomavirus (HPV) vaccine among Latino parents, to date limited information is available specific to Central American parents living in the United States (US). Therefore, this pilot cross-sectional study was designed to explore and assess Central American immigrant parents’ awareness, acceptability, and willingness to vaccinate their children against HPV, and interest in participating in future HPV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 51 publications
3
15
0
1
Order By: Relevance
“…These finding support the results of previous studies conducted with other racial and ethnic minority groups [23,31,[38][39][40][41][42] and Latinos [15][16][17][18]20,[23][24][25][26] documenting the unique and crucial influence of healthcare providers on fathers' acceptability and willingness to vaccinate their children against HPV. Although the vast majority of fathers participating in our study reported that their child's mother was the primary parent taking children to healthcare visits, fathers also mentioned close communication with their wives and/or partners about their children's health visits.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These finding support the results of previous studies conducted with other racial and ethnic minority groups [23,31,[38][39][40][41][42] and Latinos [15][16][17][18]20,[23][24][25][26] documenting the unique and crucial influence of healthcare providers on fathers' acceptability and willingness to vaccinate their children against HPV. Although the vast majority of fathers participating in our study reported that their child's mother was the primary parent taking children to healthcare visits, fathers also mentioned close communication with their wives and/or partners about their children's health visits.…”
Section: Discussionsupporting
confidence: 90%
“…Latinos are the largest minority population in the United States, and evidence indicates higher HPV-associated cancer incidence and mortality among Latinos compared to non-Hispanic whites [12,13]. Despite an increasing number of studies conducted to identify HPV awareness and acceptability of the HPV vaccine among Latinos [14][15][16][17][18][19][20][21], only very limited research is specific to Latino fathers [22][23][24][25]. The extant literature has mainly focused on Latina mothers' awareness, acceptability, and uptake of the HPV vaccine for their adolescent children, leaving fathers underrepresented in HPV research [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Eligible mothers (a) had at least one child aged 11 to 19 years, (b) self-identified as Latinx, (c) lived in Massachusetts, and (d) if foreign-born, had lived in the United States for at least 12 months. We used convenience sampling techniques to identify Latinx mothers, which included (a) posting flyers in local Latinx businesses and community-based social and health services agencies, and (b) making announcements and using visibility strategies at predominantly Spanish-speaking churches (Lindsay, Delgado, et al, 2020; Lindsay, Pineda, et al, 2020). Participants also were recruited using a snowball sampling method that involved two approaches: (a) leveraging the personal and community networks of the Latinx research staff to recruit potential participants, and (b) asking early enrollees to recommend their eligible Latinx friends (Faugier & Sargeant, 1997; Lindsay, Delgado, et al, 2020; Lindsay, Pineda, et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The studies employed qualitative and quantitative research designs and included multiple data collection methods (i.e., focus groups, semistructured interviews, and surveys; Table 1). Additional details of the studies can be found elsewhere (Lindsay, Delgado, et al, 2020; Lindsay, Le, et al, 2020; Lindsay et al, 2017; Lindsay, Pineda, et al, 2020; Lindsay, Wallington, Muñoz, & Greaney, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Latino fathers were eligible to participate if they (1) self-identified as being of Hispanic ethnicity, (2) were ≥21 years, (3) had lived in the United States for 6 or 12 months depending on study, (4) had at least one child between 2 and 8 (early childhood studies) or 11 and 19 (HPV studies) years of age, and (5) had shared parental responsibilities for or cohabitated with said child (Lindsay, Delgado, et al, 2020; Lindsay et al, 2017; Lindsay, Le, et al 2020; Lindsay, Pineda, et al, 2020; Lindsay, Wallington, Muñoz, & Greaney, 2018). In addition, in two of the studies an additional eligibility requirement included having a child enrolled in a Latino family child care home (Lindsay et al, 2017; Lindsay, Wallington, Lees, & Greaney, 2018).…”
Section: Methodsmentioning
confidence: 99%